Karakteristik Sampo Berbasis Kulit Buah Nanas (Ananas comosus) Dan Ekstrak Seledri (Apium graveolens) - Hairiyah, Nina; Lestari, Ema; Sa’diah, Sa’diah (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Pineapple skin is a waste from pineapple production which contains bromelain and flavonoid enzymes, however, its utilization is not optimal. This content has the potential to be used in shampoo preparations as an antifungal as well as an alternative solution for diverting the use of chemicals in shampoo. The shampoo preparation is added with celery extract which contains flavonoids so it is safe to be combined. This study aims to analyze the quality and level of panelists' preference for shampoo based on pineapple peel and celery extract. The research method used was starting from the preparation of materials to the manufacture of shampoo products and then testing the quality of the shampoo, namely homogeneity test, foam height test, viscosity test, pH test, density test, water content test, and antifungal activity test. Data processing on panelist liking levels uses analysis of variance. The test results of the entire sample were homogeneous, the average foam height of the entire sample was 3.83 cm, the highest viscosity was added to 7.5% coconut oil and 2.5% olive oil. Meanwhile, the highest pH value, density, and water content were added with 2.5% coconut oil and 7.5% olive oil. All samples had a positive response to antifungal activity, with the most preferred formulation being the addition of 5% coconut oil and olive oil, respectively. Analysis of variance showed that the base of pineapple peel and celery extract with the addition of coconut oil and olive oil had a significant effect on the parameters of shampoo preference Keywords : celery extract, pineapple peel, shampoo Kulit nanas merupakan limbah dari produksi nanas yang mengandung enzim bromelain dan flavonoid, namun pemanfaatannya belum optimal. Kandungan ini berpotensi untuk digunakan dalam sediaan shampo sebagai antijamur sekaligus solusi alternatif untuk mengalihkan penggunaan bahan kimia pada shampo. Sediaan shampo ditambah ekstrak seledri yang mengandung flavonoid sehingga aman untuk dipadukan. Penelitian ini bertujuan untuk menganalisis karakteristik dan tingkat kesukaan panelis terhadap sampo berbahan dasar ekstrak kulit nanas dan seledri. Metode penelitian yang digunakan dimulai dari penyiapan bahan hingga pembuatan produk shampo kemudian dilakukan pengujian kualitas shampo yaitu uji homogenitas, uji tinggi busa, uji viskositas, uji pH, uji densitas, uji kadar air, dan tes aktivitas antijamur. Pengolahan data tingkat kesukaan panelis menggunakan analisis sidik ragam. Hasil pengujian seluruh sampel homogen, rata-rata tinggi buih seluruh sampel 3,83 cm, viskositas tertinggi ditambahkan minyak kelapa 7,5% dan minyak zaitun 2,5%. Sedangkan nilai pH, densitas, dan kadar air tertinggi ditambahkan dengan minyak kelapa 2,5% dan minyak zaitun 7,5%. Semua sampel memiliki respon positif terhadap aktivitas antijamur, dengan formulasi yang paling disukai adalah penambahan minyak kelapa 5% dan minyak zaitun. Analisis variansi menunjukkan bahwa basis ekstrak kulit nanas dan seledri dengan penambahan minyak kelapa dan minyak zaitun berpengaruh nyata terhadap parameter preferensi shampo. Kata kunci : ekstrak seledri, kulit nanas, shampo